Sistem Kontrol Dan Monitoring Intensitas Cahaya dan Suhu Pada Greenhouse BerBasis IoT - Halimah Tuzsakdiah; Suhairi, M (Jurnal ELEMENTER (Elektro dan Mesin Terapan), 2023)
In general, cultivated agricultural systems in Indonesia are still in open land. However, agricultural systems that are cultivated on open land still face many problems ranging from land availability, energy, seasonal changes, pests and diseases, to crop failures faced by farmers. Actually, farmers' problems can be overcome by utilizing technology so as to get maximum yields. In this research, a greenhouse will be designed that utilizes the DHT11 sensor to read the temperature and the BH1750 sensor to read the light intensity based on the NodeMCU ESP8266. The application of this IoT-based system results in plant growth that can be controlled automatically according to the needs of the plant in order to get maximum yields. The test results for the DHT11 temperature sensor have 99.74% accuracy, and the BH1750 sensor has 92.8% accuracy. With this system, information on the condition of lettuce plants in the greenhouse can be known through the blynk application.